Methodologiacal basis of training in Physiotherapy: discussing the detachment between the training process and the work in primary health care. - Daniela Macêdo Pimentel; Cesar Cavalcanti da Silva; Eufrásio de Andrade Lima Neto (Universidade de Brasília, 2016)
From the methodological foundations underlying the training process in Physiotherapy and considering the tasks of the physiotherapist at Nucleus of Support for Family Health (FHSCs), attempted to identify the points of separation between training and use of the physiotherapist workforce in primary healthcare in João Pessoa/PB. The study is justified by the need to enhance educational processes in Physiotherapy, in order to be compatible with the requirements of their professional practice, particularly in primary healthcare level. This is an exploratory-descriptive and inferential study which quantitative approaches. Data were analyzed from the Hypothesis Test, used as method of decision making. The data analysis showed, with statistical evidences, distances between the students and teachers who say, in the process physiotherapist formation in higher education institutions surveyed, as well as differences between those who attest physiotherapist and managers in relation to the work process in FHSCs of Health Districts of the city. It was concluded that it is necessary a reformulation of methodological bases that make up educational plans related to Collective Health at the institutions which offer the course of graduation at Physiotherapy in João Pessoa, as well as a better use of the workforce of the physiotherapist with the FHSCs, aiming at a redefinition of the practices of this professional at the areas of Primary Health.